ANALISIS KESANTUNAN BERBAHASA GURU DAN SISWA KELAS XI SMAN 1 SERASAN TIMUR KABUPATEN NATUNA - Rivaldi, Viski; Madeten, Sisilya; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the application of politeness maxims according to Geoffrey Leech's theory in teacher-student, student teacher, student-student, and teacher-all-student interactions of class XI SMAN 1 Serasan Timur. The method used is descriptive qualitative with data in the form of audio recordings during learning. The results show that teacher-student interactions include 49 utterances, consisting of maxims of wisdom (17), generosity (2), appreciation (12), humility (2), consensus (11), and sympathy (1). Student-student interactions include 15 utterances: wisdom (3), generosity (2), appreciation (1), humility (1), consensus (7), and sympathy (1). Meanwhile, teacher interactions with all students only show 2 utterances of the consensus maxim and 2 of the sympathy maxim. The most frequent interactions occur between male teachers and female students, as well as female teachers and male students. The maxim of humility is the least frequent. These results are implied in learning negotiation texts for grade X SMA with a mini market simulation strategy to form polite language skills.